1987
DOI: 10.3354/meps037123
|View full text |Cite
|
Sign up to set email alerts
|

Diet changes in Scotian Shelf haddock during the pelagic and demersal phases of the first year of life

Abstract: The diet of haddock Melanograrnmus aeglefinus from the southern Scotian Shelf was studied during their first year of Me. WMe haddock were pelagic, copepods were the numerically dominant component in the diet, with a significant benthic contribution (amphipods, polychaetes) first occurring in late summer. Examination of gut contents indicated that the transition from pelagic to demersal Life occurred relatively suddenly. Catch rates did not vary with die1 periodicity and gut contents of demersal fish had few oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…The prey found in association with the bottom (e.g., harpacticoid copepods, caprellid amphipods, cumaceans) may indicate an ontogenetic transition in vertical distribution and food dependencies of these juveniles. In the Gulf of Alaska, juvenile pollock in their first winter show a marked shift toward bottom-oriented prey (Krieger, 1985;Brodeur and Wilson, 1996a), which is similar to that observed for other gadoid fishes in the Atlantic Ocean (Mahon and Neilson, 1987;Perry and Neilson, 1988). Table 2.…”
Section: Discussionsupporting
confidence: 63%
“…The prey found in association with the bottom (e.g., harpacticoid copepods, caprellid amphipods, cumaceans) may indicate an ontogenetic transition in vertical distribution and food dependencies of these juveniles. In the Gulf of Alaska, juvenile pollock in their first winter show a marked shift toward bottom-oriented prey (Krieger, 1985;Brodeur and Wilson, 1996a), which is similar to that observed for other gadoid fishes in the Atlantic Ocean (Mahon and Neilson, 1987;Perry and Neilson, 1988). Table 2.…”
Section: Discussionsupporting
confidence: 63%
“…In both groups (5 to 50 and 50 to 150 mm) cod fed initially on prey of presumably optimal size, but the size of the prey consumed did not increase with increasing fish size. Pelagic juveniles are known to continue feeding on small prey items such as copepods to the size of settlement unless larger prey items are available (Palsson 1973, 1980, Robb & Hislop 1980, Bowman 1981, Robb 1981, Mahon & Neilson 1987. However, in no other region was the size of food items of demersal juveniles reported to be as small as those from this study.…”
Section: Length Classes Of 0-group Cod [Mm)mentioning
confidence: 59%
“…Abrupt transition to the demersal habitat has previously been observed for gadoids by Koeller et al (1986) and Mahon & Neilson (1987). Through the utilization of stomach content analysis, these authors concluded that the transition period for juvenile Scotian Shelf haddock is of short duration.…”
Section: Length Classes Of 0-group Cod [Mm)mentioning
confidence: 85%
See 2 more Smart Citations